The (magic) kingdom of God - Budde, Michael (Westview Press, 1997)
Couverture de livre: Technologies the pointe Réseaux; Includes bibliographical references (p. 153-168) and index; Following Jesus in a Distraced Age; Why Culture Matters in the World Economy; The Power of Global Culture Industries; Learning the languege of Faith; How global Cuture Industries Undermine Christianity; church Barriers tu Understanding Global Culture Industries; The way from here: Radical Gospel, Radical Church